GE_GERICHTE C/21812/2015 vom 24. Mai 2017 - GE Cour de justice (2017)
PROTECTION DES DONNÉES ; PROTECTION DE LA PERSONNALITÉ ; INTÉRÊT PUBLIC ; PESÉE DES INTÉRÊTS ; BANQUE | CC.28; CC.28.a.1; LPD.12; LPD.41; LPD.6.2; CPC.168.2;